(untitled) (Móin-Móin Magazine - Studies in the Art of Puppetry, 2019)
The essay is the transcription, with some editing, of the conference-dialogue presented by two trainer/teachers of puppetry during the 3rd PRO-VOCATION - International Meeting on Training in the Arts of Puppetry, in which matters related to directing for puppet theatre, and its training, were discussed from the starting point of nine guiding questions. The dialogues approached both technical and philosophical questions about the training of directors for puppet theatre and proposed to the audience some practical experiments as well as the writing of two manifestoes about what should be taught to trainee puppet theatre directors.